The impact of political connections on innovation performance of emerging market enterprises - Hu, Siyu (2019)
In emerging markets, the government is a powerful supplementary form of market allocation of resources and plays an important role in the development of enterprises. Based on the resource-based-view (RBV) theory, this paper exams how political connections of an emerging market enterprise (EME) affecting its innovation performance and discusses how institutional contexts moderating the relationship between the political connections and firm innovation performance. Using panel data from a sample of 343 Chinese growth enterprise market (GEM) companies of Shenzhen stock exchange over 2012–2016, the empirical results show that political connections have a positive effect on firm innovation performance. And it also shows that the level of state ownership and the level of regional institutional development weakens the positive focal relationship. The study has also discussed the theoretical and managerial implications of the findings.